Downstaging in patients with hepatocellular carcinoma: Is there real hope? (Annals of Medical Research, 2021)
Aim: The conventional criteria preclude many patients with hepatocelular carcinom (HCC) from liver transplantation (LT). Recent studies reported comparable results in downstaged patients. In present study, the outcomes of patients with HCC after LT was evaluated in regard to response to a uniform downstaging protocol.Materials and Methods: The data of 136 HCC patients who underwent LT between January 2012 and April 2018 were analysed. 82 patients who were with minimum follow-up of one year and/or who reached the end-point (recurrence and/or death) were enrolled to the study and were divided into two groups as downstaging group and initially within Milan group. We retrospectively collected and then compared the baseline characteristics, postoperative complications, survival rate, and tumor recurrence rate of patients.Results: One of the study group included 54 (45.7%) patients within Milan criteria initially and there were 28 (23.7%) patients in the downstaging group. The disease-free survival rates were 82.1% and 87.1% in downstaging group and initially witihin Milan group, respectively (p=0.368). The overall 3-year survival rates were 82.1% and 88.9% in downstaging group and intially within Milan group, respectively (p=0.402).Conclusion: The patients who were initially excluded according to the current conventional criteria had a chance for LT with comparable outcome according to both the overall survival and disease-free survival rates.Keywords: Hepatocelular carcinom; liver transplantation; downstaging.
Keywords: Hepatocelular carcinom; liver transplantation; downstaging.